A method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating
Patent Information
- Application Number
- CN202610381170.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-03-26
AI Technical Summary
随着全球环保政策趋严与可持续发展理念推进,水性聚氨酯涂料逐步替代溶剂型产品,成为行业发展核心方向,但常规水性聚氨酯涂料仍存在诸多技术短板,难以满足高端自清洁、超疏水防护的使用需求;同时,传统聚氨酯原料高度依赖石油基多元醇等不可再生化石资源,生产与废弃环节环保压力大,不符合绿色低碳产业发展要求;
[0018]通过氟硅烷复配单体共价接枝改性,实现氟硅官能团均匀分布无团聚迁移,涂层具备优异且持久的超疏水自清洁性能,配合精准调控的预聚与扩链参数,涂层铅笔硬度、划格法附着力等力学性能达标,两步加水剪切分散、恒温熟化及二次过滤工艺,制得的乳液粒径均匀、成品储存稳定性优异,可适配多种基材。
Smart Images

Figure CN122103999B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyurethane coating technology, specifically a method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating. Background Technology
[0002] Polyurethane coatings, with their excellent film-forming properties, adhesion, and weather resistance, are widely used in wood protection, metal corrosion prevention, building material decoration, and outdoor facility coating, making them one of the mainstream categories in the current industrial and civil coatings market. With increasingly stringent global environmental policies and the promotion of sustainable development concepts, waterborne polyurethane coatings are gradually replacing solvent-based products, becoming a core direction for industry development. However, conventional waterborne polyurethane coatings still have many technical shortcomings, making it difficult to meet the demands for high-end self-cleaning and superhydrophobic protection. Furthermore, traditional polyurethane raw materials are highly dependent on non-renewable fossil resources such as petroleum-based polyols, resulting in significant environmental pressure during production and waste disposal, which does not meet the requirements for the development of a green and low-carbon industry.
[0003] In existing technologies, to improve the hydrophobicity and self-cleaning properties of polyurethane coatings, surface modification with organofluorine and organosilicon monomers is often used. However, these methods generally suffer from uneven distribution of fluorine and silicon functional groups and easy aggregation and migration, resulting in poor durability of hydrophobicity and rapid decline in self-cleaning effect after long-term use. Furthermore, it is difficult to simultaneously achieve good water resistance and mechanical properties. Some bio-based modification technologies attempt to replace petroleum-based components with biomass raw materials such as vegetable oils and starch. However, these biomass raw materials have drawbacks such as low reactivity and poor compatibility with the polyurethane matrix, leading to problems such as delamination, cracking, and insufficient adhesion after film formation, thus limiting their industrial application. Summary of the Invention
[0004] In view of the shortcomings of the existing technology mentioned above.
[0005] This invention provides a method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating, comprising the following steps:
[0006] Step 1: Take industrial enzymatically hydrolyzed lignin, and successively perform alkali dissolution and dispersion, acid precipitation and sedimentation, deionized water washing and filtration, and vacuum drying. Then, carry out a ring-opening grafting reaction with propylene oxide at a mass ratio of 1:3.5-4.5. The reaction vacuum degree is controlled at -0.09 to -0.095 MPa to obtain modified lignin-based polyol.
[0007] The modified lignin-based polyol was dried in a vacuum environment with a vacuum degree of -0.09 to -0.095 MPa and a temperature of 80 to 90 degrees Celsius to remove free water from the system. The drying time was 4 to 6 hours until the moisture content of the system met the process limit, thus obtaining the dried polyol.
[0008] Step 2: The prepared dry polyol and isophorone diisocyanate are added at a functional group equivalent ratio of 1:1.2-1.4 and placed in a sealed reaction vessel. High-purity nitrogen is introduced to replace the air in the vessel, and the slight positive pressure in the vessel is maintained at 0.02-0.03 MPa. The reaction is carried out at a constant temperature of 70-80 degrees Celsius until the content of free isocyanate groups in the system stabilizes and meets the standard, and then the reaction is terminated to obtain a linear polyurethane prepolymer.
[0009] Step 3: Add dimethylolpropionic acid and organotin catalyst to the obtained linear polyurethane prepolymer, maintain a slightly positive nitrogen protective atmosphere, heat to 80-85 degrees Celsius and react at a constant temperature for 2.5-3.5 hours to graft hydrophilic carboxyl groups onto the polyurethane main chain to obtain chain-extended polyurethane.
[0010] Step 4: Cool the obtained chain-extended polyurethane to 25-30 degrees Celsius, add fluorosilane complex monomers, and react at a constant temperature for 3-4 hours under a nitrogen protective atmosphere to form covalent bonds between the fluorosilicone functional groups and the hydroxyl groups of the polyurethane side chain, thus obtaining fluorosilicone modified polyurethane.
[0011] Step 5: Cool the obtained fluorosilicone modified polyurethane to 20-25 degrees Celsius, add triethylamine for neutralization reaction for 30-40 minutes to form ionized hydrophilic groups in the system, then add deionized water in batches and perform high-speed shear dispersion at 3000-4000 rpm for 20-30 minutes to obtain waterborne polyurethane emulsion.
[0012] Step 6: The prepared aqueous polyurethane emulsion is subjected to gradient vacuum distillation. The initial vacuum is -0.06 MPa, and the temperature is maintained at 35-40 degrees Celsius for 1 hour. Subsequently, the vacuum is increased to -0.095 MPa, and the temperature is maintained at 40-45 degrees Celsius for 2-3 hours. Organic solvents in the system are removed, and the solid content of the system is adjusted to the qualified range. Mechanical impurities are removed by filtering through a 200-mesh stainless steel filter to obtain the target bio-based polyurethane coating.
[0013] Drying temperature calculation steps: First, determine the highest critical temperature at which enzymatic hydrolysis of lignin does not undergo thermal decomposition through gradient temperature rise test. Combined with the change law of water boiling point decreasing with negative pressure under vacuum environment, subtract 5-8 degrees Celsius to obtain the final drying temperature.
[0014] Drying time calculation steps: Take a sample every 30 minutes to test the moisture content. When the difference between two consecutive samples of moisture content meets the process limit, it is determined that the moisture has completely evaporated, and the corresponding time is the drying time.
[0015] Prepolymerization reaction temperature calculation steps: Select the temperature corresponding to the lowest activation energy of urethane bond formation, and add 3-5 degrees Celsius above it as the isothermal reaction temperature; Isocyanate group content calculation steps:
[0016] Take a quantitative reaction solution and react it fully with excess di-n-butylamine. Titrate the remaining di-n-butylamine with standard hydrochloric acid solution. Calculate the actual isocyanate content directly by the volume difference of hydrochloric acid consumed. Calculation steps for vacuum distillation parameters: Match the corresponding vacuum degree according to the volatility characteristics of acetone to ensure that the solvent evaporates slowly and the emulsion does not break.
[0017] The technical solutions provided by the embodiments of this disclosure have at least the following beneficial effects:
[0018] By covalently grafting fluorosilane composite monomers, uniform distribution of fluorosilicone functional groups without agglomeration and migration is achieved. The coating has excellent and long-lasting superhydrophobic self-cleaning properties. With precise control of prepolymerization and chain extension parameters, the mechanical properties of the coating, such as pencil hardness and cross-cut adhesion, meet the standards. The two-step water addition shear dispersion, constant temperature curing and secondary filtration process produces an emulsion with uniform particle size and excellent storage stability, which can be adapted to a variety of substrates. Attached Figure Description
[0019] Figure 1 This is a flowchart of the present invention. Detailed Implementation
[0020] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] Please see Figure 1 A method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating is proposed, comprising the following steps:
[0022] Step 1: Take industrial enzymatically hydrolyzed lignin, and successively perform alkali dissolution and dispersion, acid precipitation and sedimentation, deionized water washing and filtration, and vacuum drying. Then, carry out a ring-opening grafting reaction with propylene oxide at a mass ratio of 1:3.5-4.5. The reaction vacuum degree is controlled at -0.09 to -0.095 MPa to obtain modified lignin-based polyol.
[0023] The modified lignin-based polyol was dried in a vacuum environment with a vacuum degree of -0.09 to -0.095 MPa and a temperature of 80 to 90 degrees Celsius to remove free water from the system. The drying time was 4 to 6 hours until the moisture content of the system met the process limit, thus obtaining the dried polyol.
[0024] Step 2: The prepared dry polyol and isophorone diisocyanate are added at a functional group equivalent ratio of 1:1.2-1.4 and placed in a sealed reaction vessel. High-purity nitrogen is introduced to replace the air in the vessel, and a slight positive pressure of 0.02-0.03 MPa is maintained in the vessel. The reaction is carried out at a constant temperature of 70-80 degrees Celsius until the content of free isocyanate groups in the system stabilizes and meets the standard, and then the reaction is terminated to obtain a linear polyurethane prepolymer.
[0025] Step 3: Add dimethylolpropionic acid and organotin catalyst to the obtained linear polyurethane prepolymer, maintain a slightly positive nitrogen protective atmosphere, heat to 80-85 degrees Celsius and react at a constant temperature for 2.5-3.5 hours to graft hydrophilic carboxyl groups onto the polyurethane backbone to obtain chain-extended polyurethane.
[0026] Step 4: Cool the obtained chain-extended polyurethane to 25-30 degrees Celsius, add fluorosilane complex monomers, and maintain a constant temperature reaction under a nitrogen protective atmosphere for 3-4 hours to allow the fluorosilicone functional groups to form covalent bonds with the hydroxyl groups of the polyurethane side chains, thus obtaining fluorosilicone modified polyurethane.
[0027] Step 5: Cool the obtained fluorosilicone modified polyurethane to 20-25 degrees Celsius, add triethylamine to neutralize and react for 30-40 minutes to form ionized hydrophilic groups in the system, then add deionized water in batches and disperse at high speed of 3000-4000 rpm for 20-30 minutes to obtain waterborne polyurethane emulsion.
[0028] Step 6: Perform gradient vacuum distillation on the prepared waterborne polyurethane emulsion. Initially, maintain a vacuum of -0.06 MPa and a temperature of 35-40 degrees Celsius for 1 hour. Subsequently, increase the vacuum to -0.095 MPa and maintain a temperature of 40-45 degrees Celsius for 2-3 hours to remove organic solvents from the system. Adjust the solid content of the system to the qualified range. Filter through a 200-mesh stainless steel filter to remove mechanical impurities and obtain the target bio-based polyurethane coating.
[0029] Drying temperature calculation steps: First, determine the highest critical temperature at which enzymatic hydrolysis of lignin does not undergo thermal decomposition through gradient temperature rise test. Combined with the change law of water boiling point decreasing with negative pressure under vacuum environment, subtract 5-8 degrees Celsius to obtain the final drying temperature.
[0030] Drying time calculation steps: Take a sample every 30 minutes to test the moisture content. When the difference between two consecutive samples of moisture content meets the process limit, it is determined that the moisture has completely evaporated, and the corresponding time is the drying time.
[0031] Prepolymerization reaction temperature calculation steps: Select the temperature corresponding to the lowest activation energy of urethane bond formation, and add 3-5 degrees Celsius above it as the isothermal reaction temperature; Isocyanate group content calculation steps:
[0032] Take a quantitative reaction solution and react it fully with excess di-n-butylamine. Titrate the remaining di-n-butylamine with standard hydrochloric acid solution. Calculate the actual isocyanate content directly by the volume difference of hydrochloric acid consumed. Calculation steps for vacuum distillation parameters: Match the corresponding vacuum degree according to the volatility characteristics of acetone to ensure that the solvent evaporates slowly and the emulsion does not break.
[0033] As an optional embodiment, the specific steps of the raw material processing in step 1 are as follows:
[0034] Industrial enzymatically hydrolyzed lignin was dispersed using an aqueous sodium hydroxide solution at a liquid-to-solid ratio of 8-10:1, and stirred at 60-70 degrees Celsius for 1.5-2 hours until the lignin was completely dissolved.
[0035] Hydrochloric acid solution was slowly added dropwise to the dispersion to adjust the pH of the system to the isoelectric point range of lignin. The mixture was allowed to stand for 60-90 minutes until the lignin was completely precipitated. The precipitate was washed with deionized water until the filtrate was neutral. The precipitate was then vacuum dried at 85-90 degrees Celsius to constant weight to obtain purified lignin.
[0036] The purified lignin was mixed with propylene oxide at a hydroxyl equivalent ratio of 1:3.2-3.8, and potassium hydroxide was added to meet the catalytic requirements. The mixture was reacted at 75-85 degrees Celsius in a closed environment for 4-5 hours until the phenolic hydroxyl grafting conversion rate reached the target.
[0037] The reaction product was subjected to vacuum distillation to remove unreacted propylene oxide, yielding a modified lignin-based polyol.
[0038] Steps for calculating the isoelectric point of lignin: Gradually adjust the pH of the dispersion while simultaneously detecting the system potential. The pH at which the potential approaches zero and the lignin settles rapidly is the isoelectric point of the lignin.
[0039] Steps for calculating the hydroxyl value of polyols: Weigh a quantitative amount of modified polyol and react it with the acetylation reagent. After hydrolyzing the remaining reagent, titrate with alkaline solution. Calculate the hydroxyl value directly using the titration volume, sample mass, and alkaline solution concentration.
[0040] Number average molecular weight calculation steps: Test the elution curve by gel permeation chromatography, compare it with the standard sample curve, and calculate the average molecular chain length by peak area weighting; Moisture content calculation steps: Weigh a quantitative amount of polyol, vacuum dry it to constant weight, and divide the mass difference before and after drying by the initial mass to obtain the actual moisture content.
[0041] As an optional embodiment, in step 2:
[0042] The functional group equivalent ratio of dry polyol to isophorone diisocyanate is used to determine the target molecular weight range of linear polyurethane prepolymer.
[0043] Nitrogen purging is performed 3-4 times to ensure that the residual air in the container meets the process requirements.
[0044] The nitrogen pressure inside the container was maintained at a stable slightly positive pressure of 0.02-0.03 MPa;
[0045] The prepolymerization reaction is carried out at a stirring speed of 200-300 rpm throughout to avoid local accumulation of materials in the system. The reaction is terminated when the free isocyanate content stabilizes and meets the standard, thus obtaining a linear polyurethane prepolymer with a regular structure.
[0046] Functional group equivalent ratio calculation steps: Based on the previously measured hydroxyl value of the polyol, calculate the number of moles of hydroxyl groups per unit mass of polyol. Combined with the target chain length of the prepolymer, match the number of moles of isocyanate in isophorone diisocyanate. The ratio of these two is the required functional group equivalent ratio; Nitrogen micro-positive pressure calculation steps:
[0047] The minimum critical pressure is determined based on just preventing outside air from seeping into the reaction vessel; the stirring speed calculation steps are as follows: combining the reactor volume, the size of the stirring paddle and the viscosity of the system, calculate the minimum speed at which the material is completely suspended and there is no sedimentation; the isocyanate equivalent value calculation steps are as follows: combining the target molecular weight of the prepolymer, calculate the free isocyanate content that needs to be retained to terminate the reaction according to the stepwise polymerization law.
[0048] As an optional embodiment, in step 3:
[0049] The amount of dimethylolpropionic acid added meets the requirements of the hydrophilic chain extension process. The organotin catalyst selected is dibutyltin dilaurate, and the amount added is sufficient for catalyst addition.
[0050] Dimethylolpropionic acid was completely dissolved in anhydrous acetone and stirred until no solute remained. The solution was then slowly added dropwise to the prepolymer at a rate of 5-8 mL per minute, with stirring throughout the addition process to avoid excessively high local concentrations. After the addition was complete, the chain was extended at a constant temperature until the chain extension reaction was complete and the viscosity of the system stabilized at 5000-6000 mPa·s.
[0051] Steps for calculating the amount of dimethylolpropionic acid added: Determine the hydrophilic group density based on the emulsion dispersion stability, combine it with the molar mass of the prepolymer, and directly calculate the required mass of dimethylolpropionic acid according to the equivalent matching relationship between carboxyl groups and isocyanates; Steps for calculating the dropping rate:
[0052] The total volume of the solution is evenly distributed to the early stage of chain extension to ensure that the amount added per unit time does not exceed the system's reaction capacity and to prevent local high concentrations from causing side reactions. The viscosity calculation steps are as follows: During the chain extension reaction, the molecular chain continues to grow and the viscosity increases synchronously. The reaction progress is determined by real-time viscosity detection and the linear relationship between chain length and viscosity.
[0053] As an optional embodiment, in step 4:
[0054] The fluorosilane compound monomer is composed of heptadecafluorodecyltrimethoxysilane and vinyltriethoxysilane in a molar ratio of 1:1, and the total amount of compound monomer added meets the requirements of the fluorosilicone grafting process.
[0055] The compound monomers are premixed evenly and added dropwise at a rate of 3-5 ml per minute under constant temperature of 25-30 degrees Celsius. After the addition is completed, the reaction is carried out at a constant temperature until the residual amount of hydroxyl groups reaches the standard, ensuring that the fluorosilicone functional groups and the side chain hydroxyl groups are completely covalently bonded and that the interfacial groups are uniformly arranged.
[0056] Calculation steps for fluorosilicone compound ratio: Determine the molar ratio based on the reactivity ratio of the two monomers to ensure simultaneous grafting without competition or deviation, and to meet the requirement of uniform distribution at the coating interface; Calculation steps for total amount of compound monomers added:
[0057] Based on the molar number of hydroxyl groups in the side chain of the extended polyurethane, and according to the equivalent reaction relationship between hydroxyl groups and siloxane groups, the total mass of monomers required is directly calculated. The steps for calculating the full grafting time are as follows: sample and test the residual amount of hydroxyl groups every hour until the hydroxyl content no longer decreases, which is the full bonding time.
[0058] As an optional embodiment, in step 5:
[0059] The molar ratio of triethylamine to hydrophilic carboxyl groups was 1:1, and the pH of the system after neutralization was controlled in the neutral to slightly alkaline range. High-speed shear dispersion was carried out using a two-step water addition method. First, some deionized water was added to complete the primary dispersion, and shear dispersion was carried out at 3000 rpm for 10 minutes. Then, the remaining deionized water was added to refine the particle size, and shear dispersion was carried out at 4000 rpm for 15-20 minutes. The temperature was maintained at 20-25 degrees Celsius throughout the dispersion process, resulting in a monodisperse waterborne polyurethane emulsion with a median particle size of 150-200 nanometers.
[0060] Triethylamine addition calculation steps: Based on the total molar number of hydrophilic carboxyl groups, the required mass of triethylamine is directly calculated using the equimolar neutralization principle to ensure complete ionization of the hydrophilic groups; Shear speed calculation steps: In the first stage, low-speed shearing completes the initial nucleation of latex particles; in the second stage, the speed is increased according to the target particle size, with smaller particle sizes requiring higher speeds; Step-by-step water addition calculation steps: First, a small amount of water is added to complete the initial nucleation, and then the remaining water is added to achieve stable dispersion of the system. The water addition ratio is dynamically adjusted according to the emulsion viscosity;
[0061] As an optional embodiment, in step 6:
[0062] Gradient vacuum distillation controls process parameters throughout to avoid emulsion foaming and demulsification. The solvent residue after distillation meets environmental and process limits. The solid content of the system is adjusted to a stable and qualified range. A 200-mesh stainless steel filter is used to completely remove gel impurities from the system, yielding crude waterborne polyurethane coating.
[0063] Gradient vacuum parameter calculation steps: The initial vacuum level is slowly increased, based on the premise that the emulsion does not foam and the solvent evaporates steadily; subsequently, the vacuum level is gradually increased until the solvent is completely removed. Solid content calculation steps:
[0064] Weigh a quantitative amount of emulsion and dry it to constant weight. Divide the dry material mass by the wet material mass to obtain the actual solid content. Add deionized water as needed to adjust to the target value. Solvent residual time calculation steps: Take a sample every 1 hour to detect the solvent evaporation until the evaporation approaches zero, which is the time for complete solvent removal.
[0065] As an optional embodiment, in steps 1 to 6, anhydrous acetone is used as the single solvent, the amount of solvent added meets the dissolution requirements of the entire reaction, and the acetone is recovered in the whole process by vacuum distillation, and the recovery efficiency meets the process requirements; the obtained linear polyurethane prepolymer has no redundant branches, and the fluorosilicone functional groups are uniformly distributed on the polyurethane side chains through continuous uniform drop addition and constant temperature stirring process.
[0066] Acetone recovery efficiency calculation steps: Collect the condensed and recovered acetone and weigh it. Divide the recovered mass by the initial total mass of acetone feed to obtain the actual recovery efficiency. Functional group uniformity determination: Uniform distribution is achieved by relying on the previous continuous proportioning, uniform dripping and constant temperature stirring process. There are no additional independent control steps. The uniformity is completely guaranteed by the previous continuous process.
[0067] As an optional embodiment, the prepared bio-based polyurethane coating is applied at room temperature to form a film, and the dry film thickness is controlled at 30-40 micrometers.
[0068] Furthermore, the dry film's water contact angle and roll-off angle both meet the relevant superhydrophobic indicators. The coating's cross-cut adhesion and pencil hardness meet the application standards. After immersion in water at room temperature for 72 hours, there is no bubbling, peeling, or whitening, and the water resistance meets the standards.
[0069] The target dry film thickness is calculated by multiplying the coating amount per unit area by the solid content controlled by the solvent removal and refining process, multiplying the coating amount by the solid content, and then dividing by the coating density. The coating surface performance calculation steps are as follows: Based on the uniform distribution of fluorosilicone functional groups and combined with the conventional laws of interfacial tension, the contact angle and roll-off angle are directly calculated. The mechanical property determination steps are as follows: The core parameters of prepolymer chain length, chain extension density, and fluorosilicone grafting rate are integrated to comprehensively determine the molecular crosslinking density and chain segment rigidity, thereby determining the adhesion and hardness.
[0070] As an optional embodiment, the following steps are also included:
[0071] After the crude coating has been desolventized and refined, it is subjected to closed, constant temperature and light-proof curing. The curing temperature is 22-26 degrees Celsius and the curing time is 24 hours. During the curing process, the latex particles are stirred at a low speed of 50-60 revolutions per minute in a closed environment to avoid damage.
[0072] After maturation, it is filtered a second time through a 200-mesh stainless steel filter to remove trace amounts of gel impurities produced during maturation.
[0073] Trace amounts of gel impurities produced during aging are removed to obtain a finished bio-based polyurethane coating with satisfactory storage stability and uniform performance.
[0074] Based on the stable properties of waterborne polyurethane colloids, the critical temperature for room temperature and protection from light was selected. According to the requirement of complete release of internal stress in the emulsion, the 24-hour curing time was determined. The low-speed stirring speed was calculated: based on the premise of not damaging the latex particle structure and not causing demulsification, the low speed range was determined. The secondary filtration used a filter with the same pore size as the solvent removal and refining process.
[0075] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and comparative examples. The raw materials used in the embodiments are all commercially available industrial-grade products, and the performance testing methods are carried out in accordance with national coating standards. The parameters of the embodiments are all taken from the range described in the claims. The comparative examples are used to compare and demonstrate the technical advantages of the present invention.
[0076] Example 1;
[0077] A method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating, the specific steps of which are as follows:
[0078] Step 1: Industrial enzymatically hydrolyzed lignin was dispersed in a 12wt% sodium hydroxide aqueous solution at a liquid-to-solid ratio of 9:1 and stirred at 65°C for 1.8 hours until the lignin was completely dissolved. 11wt% hydrochloric acid solution was slowly added dropwise to adjust the pH to the isoelectric point of the lignin. The mixture was allowed to stand for 75 minutes until complete sedimentation. The filtrate was washed with deionized water until neutral and then vacuum-dried at 88°C to constant weight to obtain purified lignin. The purified lignin was then subjected to a ring-opening grafting reaction with propylene oxide at a mass ratio of 1:4 under a vacuum of -0.092 MPa. Potassium hydroxide (1.8wt% of the purified lignin mass) was added as a catalyst, and the reaction was carried out in a sealed environment at 80°C for 4.5 hours. Unreacted propylene oxide was removed by vacuum distillation to obtain modified lignin-based polyol. The polyol was then dried under vacuum at -0.092 MPa and 85°C for 5 hours until the moisture content met the process limit, yielding dried polyol.
[0079] Step 2: Add the dried polyol and isophorone diisocyanate at a functional group equivalent ratio of 1:1.3, place them in a sealed reaction vessel, purge with high-purity nitrogen three times, maintain a slight positive pressure of 0.025 MPa, and react at a constant temperature of 75 degrees Celsius until the content of free isocyanate groups stabilizes and meets the standard, thus obtaining a linear polyurethane prepolymer. The stirring speed is 250 rpm throughout the process.
[0080] Step 3: Add dimethylolpropionic acid and dibutyltin dilaurate catalyst to the prepolymer, maintain a slight positive pressure of nitrogen, and heat to 82 degrees Celsius for 3 hours. Dimethylolpropionic acid is dissolved in anhydrous acetone beforehand and added dropwise at a rate of 6 ml per minute until the viscosity of the system stabilizes at 5500 mPa·s, thus obtaining chain-extended polyurethane.
[0081] Step 4: Cool the chain-extended polyurethane to 28 degrees Celsius, add a fluorosilicone monomer compounded with heptadecafluorodecyltrimethoxysilane and vinyltriethoxysilane in a molar ratio of 1:1, add dropwise at a rate of 4 ml per minute, and react at a constant temperature for 3.5 hours under nitrogen protection until the residual hydroxyl content reaches the standard, thus obtaining the fluorosilicone modified polyurethane.
[0082] Step 5: Cool to 23 degrees Celsius, add triethylamine and neutralize for 35 minutes, with a molar ratio of triethylamine to hydrophilic carboxyl groups of 1:1; use a two-step water addition method, first add 40% deionized water and shear disperse at 3000 rpm for 10 minutes, then add the remaining 60% deionized water and shear disperse at 4000 rpm for 18 minutes to obtain a monodisperse waterborne polyurethane emulsion.
[0083] Step 6: Gradient vacuum distillation, initial vacuum of -0.06 MPa, 38 degrees Celsius for 1 hour, then increase vacuum to -0.095 MPa, 42 degrees Celsius for 2.5 hours to remove organic solvents, adjust solid content to the qualified range, filter through a 200-mesh filter to obtain crude coating; aging at 24 degrees Celsius in the dark for 24 hours with stirring speed of 55 rpm, then filter again through a 200-mesh filter to obtain finished coating.
[0084] Example 2;
[0085] The difference from Example 1 is that in step 1, the mass ratio of purified lignin to propylene oxide is 1:3.5, the drying temperature is 80 degrees Celsius, and the drying time is 4 hours; in step 2, the functional group equivalent ratio is 1:1.2, and the reaction temperature is 70 degrees Celsius; the remaining steps and parameters are consistent with the claims, and the finished coating is obtained.
[0086] Example 3;
[0087] The difference from Example 1 is that in step 1, the mass ratio of purified lignin to propylene oxide is 1:4.5, the drying temperature is 90 degrees Celsius, and the drying time is 6 hours; in step 2, the functional group equivalent ratio is 1:1.4, and the reaction temperature is 80 degrees Celsius; the remaining steps and parameters are consistent with the claims, and the finished coating is obtained.
[0088] Comparative example;
[0089] Comparative Example 1: A coating was prepared by replacing the lignin-based polyol of the present invention with a traditional petroleum-based polyether polyol, while keeping the other processes and parameters the same as in Example 1.
[0090] Comparative Example 2: Step 4, the fluorosilicone grafting process, was omitted, and the remaining processes and parameters were the same as in Example 1, resulting in a conventional waterborne polyurethane coating.
[0091] Comparative Example 3: A coating was prepared using conventional lignin modification technology without precise purification and vacuum drying. The remaining processes and parameters were the same as in Example 1.
[0092] Performance test results
[0093] Water contact angle Meets standards (superhydrophobic) Meets standards (superhydrophobic) Meets standards (superhydrophobic) Not up to superhydrophobic standard Ordinary hydrophobic, no self-cleaning properties Approaching hydrophobicity standards, but with poor stability. Pencil hardness 2H 2H 2H H H HB Cross-cut adhesion Level 0 Level 0 Level 0 Level 1 Level 1 Level 2 Soaking in water at room temperature for 72 hours No bubbling, no peeling, no whitening No bubbling, no peeling, no whitening No bubbling, no peeling, no whitening Slightly white Noticeable bubbling and whitening Severe peeling and whitening Storage stability (at room temperature) No stratification for ≥6 months No stratification for ≥6 months No stratification for ≥6 months 3 months of slight stratification 2 months of clear stratification Severe stratification in 1 month
[0094] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating, characterized in that, Includes the following steps: Step 1: Take industrial enzymatically hydrolyzed lignin, and successively perform alkali dissolution and dispersion, acid precipitation and sedimentation, deionized water washing and filtration, and vacuum drying. Then, carry out a ring-opening grafting reaction with propylene oxide at a mass ratio of 1:3.5-4.
5. The reaction vacuum degree is controlled at -0.09 to -0.095 MPa to obtain modified lignin-based polyol. The modified lignin-based polyol was dried in a vacuum environment with a vacuum degree of -0.09 to -0.095 MPa and a temperature of 80 to 90 degrees Celsius to remove free water from the system. The drying time was 4 to 6 hours until the moisture content of the system met the process limit, thus obtaining the dried polyol. Step 2: The prepared dry polyol and isophorone diisocyanate are added at a functional group equivalent ratio of 1:1.2-1.4 and placed in a sealed reaction vessel. High-purity nitrogen is introduced to replace the air in the vessel, and a slight positive pressure of 0.02-0.03 MPa is maintained in the vessel. The reaction is carried out at a constant temperature of 70-80 degrees Celsius until the content of free isocyanate groups in the system stabilizes and meets the standard. The reaction is then terminated to obtain isocyanate-terminated polyurethane prepolymer. Step 3: Add dimethylolpropionic acid and organotin catalyst to the isocyanate-terminated polyurethane prepolymer, maintain a slightly positive nitrogen protective atmosphere, heat to 80-85 degrees Celsius and react at a constant temperature for 2.5-3.5 hours to graft hydrophilic carboxyl groups onto the polyurethane main chain to obtain chain-extended polyurethane. Step 4: Cool the obtained chain-extended polyurethane to 25-30 degrees Celsius, add fluorosilane complex monomers, and maintain a constant temperature reaction under a nitrogen protective atmosphere for 3-4 hours to allow the fluorosilicone functional groups to form covalent bonds with the hydroxyl groups of the polyurethane side chains, thus obtaining fluorosilicone modified polyurethane. Step 5: Cool the obtained fluorosilicone modified polyurethane to 20-25 degrees Celsius, add triethylamine to neutralize and react for 30-40 minutes to form ionized hydrophilic groups in the system, then add deionized water in batches and disperse at high speed of 3000-4000 rpm for 20-30 minutes to obtain waterborne polyurethane emulsion. Step 6: The prepared aqueous polyurethane emulsion is subjected to gradient vacuum distillation. The initial vacuum degree is -0.06 MPa and the temperature is 35-40 degrees Celsius for 1 hour. Subsequently, the vacuum degree is increased to -0.095 MPa and the temperature is 40-45 degrees Celsius for 2-3 hours to remove organic solvents from the system. The solid content of the system is adjusted to the qualified range. Mechanical impurities are removed by filtering through a 200-mesh stainless steel filter to obtain the target bio-based polyurethane coating. The fluorosilane compound monomer is prepared by compounding heptadecafluorodecyltrimethoxysilane and vinyltriethoxysilane in a molar ratio of 1:
1. The compound monomers are premixed evenly and added dropwise at a rate of 3-5 ml per minute under constant temperature of 25-30 degrees Celsius to ensure that the fluorosilicone functional groups and the side chain hydroxyl groups are completely covalently bonded and to achieve uniform arrangement of interfacial groups.
2. The method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating according to claim 1, characterized in that, The specific steps of the raw material processing in step 1 are as follows: Industrial enzymatically hydrolyzed lignin was dispersed using an aqueous sodium hydroxide solution at a liquid-to-solid ratio of 8-10:1, and stirred at 60-70 degrees Celsius for 1.5-2 hours until the lignin was completely dissolved. Hydrochloric acid solution was slowly added dropwise to the dispersion to adjust the pH of the system to the isoelectric point range of lignin. The mixture was allowed to stand for 60-90 minutes until the lignin was completely precipitated. The precipitate was washed with deionized water until the filtrate was neutral. The precipitate was then vacuum dried at 85-90 degrees Celsius to constant weight to obtain purified lignin.
3. The method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating according to claim 2, characterized in that, In step 2: The prepolymerization reaction is carried out at a stirring speed of 200-300 rpm throughout to avoid local accumulation of materials in the system. The reaction is terminated when the free isocyanate content is stable and meets the standard, thus obtaining an isocyanate-terminated polyurethane prepolymer.
4. The method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating according to claim 3, characterized in that, In step 3: The organotin catalyst selected is dibutyltin dilaurate; Dimethylolpropionic acid was completely dissolved in anhydrous acetone and stirred until no solute remained. The solution was then slowly added dropwise to the prepolymer at a rate of 5-8 mL per minute, with stirring throughout the addition process to avoid excessively high local concentrations. After the addition was complete, the chain was extended at a constant temperature until the chain extension reaction was complete and the viscosity of the system stabilized at 5000-6000 mPa·s.
5. The method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating according to claim 4, characterized in that, In step 5: The molar ratio of triethylamine to hydrophilic carboxyl groups was 1:1, and the pH of the system after neutralization was controlled in the neutral to slightly alkaline range. High-speed shear dispersion adopted a two-step water addition method. First, some deionized water was added to complete the primary dispersion, and shear dispersion was carried out at 3000 rpm for 10 minutes. Then, the remaining deionized water was added to refine the particle size, and shear dispersion was carried out at 4000 rpm for 15-20 minutes. The temperature was maintained at 20-25 degrees Celsius throughout the dispersion process to obtain a monodisperse waterborne polyurethane emulsion with a median particle size of 150-200 nanometers.
6. The method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating according to claim 1, characterized in that, In steps 1 to 6, anhydrous acetone is used as the sole solvent, and the amount of solvent added meets the dissolution requirements of the entire reaction. The acetone is recovered throughout the process by vacuum distillation, and the recovery efficiency meets the process requirements.
7. The method for preparing a bio-based superhydrophobic polyurethane self-cleaning coating according to claim 1, characterized in that, It also includes the following steps: The coating obtained in step 6 is subjected to closed, constant temperature and light-proof curing at a curing temperature of 22-26 degrees Celsius for 24 hours. During the curing process, the coating is stirred in a closed environment at a low speed of 50-60 revolutions per minute to avoid damage to the latex particles. After maturation, it is filtered a second time through a 200-mesh stainless steel filter.
Citation Information
Patent Citations
Lignin-based polyol for synthesizing polyurethane and preparation method of lignin-based polyol
CN112778540A
Lignin-based waterborne polyurethane as well as preparation method and application thereof
CN119955062A
